Socialization of the Power Relationship of Village Heads and Village Consultational Boards (BPD) in Village Government - Nain, Umar; Rosliana, Rosliana; Ibrahim, Suaib (Journal of Universal Community Empowerment Provision, 2024)
The importance of better understanding the power relations between the Village Head and the Village Consultative Body (BPD) in the context of village government administration. Through socialization activities in Towata Village, North Polong Bangkeng District, Takalar Regency, participants, especially the main elements such as the Village Head, Chairman and BPD Members, gained a deeper understanding of the role and authority of each party as well as the positive impact of creating positive relationships. balance between the two. The results of the socialization show increased awareness of the importance of harmonious cooperation between the Village Head and the BPD in decision making, implementing village programs, and monitoring the performance of the village head. In addition, a better understanding of these power relations also opens up opportunities to resolve conflicts or tensions that may arise within village government. Thus, this paper concludes that a better understanding of the power relations between Village Heads and BPD is an important first step in building effective, fair and democratic village governance.